Numerical Investigation on the Performance of Proton Exchange Membrane Fuel Cell With Zigzag Flow Channels - Zhang, Shuanyang; Liu, Shun; Xu, Hongtao; Mao, Yijun; Wang, Ke (Frontiers in Thermal Engineering, 2022)
Reasonable flow channel designs play a significant role in improving the performance of proton exchange membrane fuel cells (PEMFC). The effect of the zigzag flow channels with three different numbers of turns on the performance of PEMFC was investigated in this paper. The polarization curves, molar concentration of oxygen and water, and power density were analyzed, and the numerical results showed that the overall performance of the zigzag flow channels was significantly better than that of the conventional parallel flow channel. With the increase of the number of turns from 3 to 9, the performance of PEMFC was gradually improved, the diffusion capacity of oxygen to the interface of the electrochemical reaction was also promoted, and the low oxygen concentration regions were gradually reduced. When the number of turns was 9, the current density of PEMFC was 8.85% higher than that of the conventional parallel channel at the operating voltage of 0.4 V, and the oxygen non-uniformity at the between gas diffusion layer (GDL) and catalyst layer (CL) interface was the minimum with a value of 0.51. In addition, the molar concentration of water in the channel also decreased. Due to the relatively large resistance of the zigzag flow channels, the maximum pressure drop of the zigzag flow channel was 263.5 Pa, which was also conducive to the improvement of the drainage effect of the conventional parallel flow channel. With the increase of the number of turns in the zigzag channel, the pressure drop and parasitic power density gradually increased. The 9-zigzag flow channel obtained the maximum pressure drop and net power density, which were 263.5 Pa and 2995.6 W/m2 respectively.